2014
DOI: 10.18632/oncotarget.2486
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 leads to attenuation of apoptosis through Bax heterodimerization in human thyroid carcinoma cells

Abstract: Cancer cells survive escaping normal apoptosis and the blocks in apoptosis that keep cancer cells alive are promising candidates for targeted therapy. Galectin-3 (Gal-3) is, a member of the lectin family, which is involved in cell growth, adhesion, proliferation and apoptosis. It remains elusive to understand the role of Gal-3 on apoptosis in thyroid carcinoma cells. Here, we report that Gal-3 heterodimerizes Bax, mediated by the carbohydrate recognition domain (CRD) of Gal-3, leading to anti-apoptotic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 34 publications
3
50
1
Order By: Relevance
“…In our studies , we have observed leukemia cells can also induce Galectin 3 in MSC suggesting that the induction of Galectin 3 between cells can be mutual (Ruvolo et al unpublished).Galectin 3 Intracellular functionsGalectin 3 as an anti-apoptotic moleculeGalectin 3 can function as an anti-apoptotic molecule(19,(27)(28)(29)(30)(77)(78)(79)(80)(81)(82)(83). Galectin 3 influences many diverse signal transduction cascades and pro-survival processes that include major oncogenes such as RAS, BCL2, and MYC(19,(27)(28)(29)(30)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). The tumor suppressor function of anti-apoptotic function is important in some cancer cells(85,(93)(94)(95)(96).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In our studies , we have observed leukemia cells can also induce Galectin 3 in MSC suggesting that the induction of Galectin 3 between cells can be mutual (Ruvolo et al unpublished).Galectin 3 Intracellular functionsGalectin 3 as an anti-apoptotic moleculeGalectin 3 can function as an anti-apoptotic molecule(19,(27)(28)(29)(30)(77)(78)(79)(80)(81)(82)(83). Galectin 3 influences many diverse signal transduction cascades and pro-survival processes that include major oncogenes such as RAS, BCL2, and MYC(19,(27)(28)(29)(30)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). The tumor suppressor function of anti-apoptotic function is important in some cancer cells(85,(93)(94)(95)(96).…”
mentioning
confidence: 64%
“…In cancers where Galectin 3 has been found to have some role in the malignancy, it will be important to identify changes in glycosylation of the glycoproteins and glycolipids that are known to associate with Galectin 3. shown to regulate BCL2 and other BCL2 family members by directly binding these molecules (30,79). In addition, suppression of Galectin 3 has been shown to reduce BCL2 protein levels in colon cancer cells though the mechanism involved is not clear (78).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Interestingly, benign thyroid proliferations (nodular hyperplasia and adenoma) do not express this marker (8)(9)(10)(11)(12)(13). This fact, together with a strong biologic rationale, which explains the restricted expression of gal-3 in thyroid cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), prompted us to explore the possibility to image thyroid cancer in vivo by using Gal-3 immunoPET. The imaging method we propose combines the high sensitivity and resolution of a PET camera with the biomolecular specificity of Gal-3 mAb for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of Gal-3 expression (via mRNA interference) reverts the transformed phenotype in a papillary thyroid carcinoma cell line and in a breast carcinoma cell line as well (15,16); (iii) the aberrant expression of Gal-3 in thyroid follicular cells blocks the apoptotic program, a feature that favors the development of cancer (17)(18)(19); (iv) Gal-3 is a physiologic target of p53 transcriptional activity and p53-mediated downregulation of Gal-3 is required for p53-induced apoptosis (20); (v) genetic studies provide the evidence that the hypomethylation state of 5 CpG sites in the Gal-3 gene is highly associated with thyroid malignancies (21); (vi) an immunohistocytochemical test method based on Gal-3 expression analysis has been developed for improving the diagnostic accuracy of conventional thyroid FNA cytology and histology (8,9,(22)(23)(24). The method has been validated for clinical use in two large multicenter studies (8,9).…”
Section: The Use Of Pet In Combination With Different Pet Tracers Likmentioning
confidence: 99%
“…Following apoptotic stimuli, Galectin-3 translocates from either the cytosol or the nucleus to the mitochondria (4), where it interacts with Bcl-2 and blocks the alteration of mitochondrial membrane potential and cytochrome-c release (71). It has also been reported that Galectin-3 heterodimerizes with Bax, mediated by the carbohydrate recognition domain of Galectin-3, which leads to attenuation of apoptosis in human thyroid carcinoma cells (76). Further, this galectin is an important antiapoptotic effector molecule that confers resistance to conventional cancer chemotherapy.…”
Section: Protumourigenic Role Of Galectin3mentioning
confidence: 99%